FRI0210 Extra-articular manifestations are associated with worse quality of life and clinical outcome in patients with axial spondyloarthritis. (12th June 2018) - van der Meer, R.; Arends, S.; Kruidhof, S.; Bos, R.; Bootsma, H.; Wink, F.; Spoorenberg, A.
Abstract : Background: In the 1960s, the association between axial spondyloarthritis (SpA) and extra-articular manifestations (EAMs), acute anterior uveitis (AAU), inflammatory bowel disease (IBD) and psoriasis, was first reported. Still, knowledge of axial SpA disease outcome associated with the development of EAMs is scarce. Objectives: To investigate the prevalence and 4 year incidence of EAMs and to explore associations of newly developed EAMs with disease outcome after 4 years of follow-up in a large cohort of axial SpA patients. Methods: All consecutive patients fulfilling the modified New York criteria for AS or the ASAS criteria for axial SpA from the prospective observational Groningen Leeuwarden Axial Spondyloarthritis (GLAS) cohort with a baseline visit between November 2004 and December 2011 were included in the analyses. Baseline and follow-up data of EAMs from the GLAS database were verified in the medical records. EAMs were only recorded and used for analyses when a description of the diagnosis by an ophthalmologist, gastroenterologist or dermatologist was present. Prevalence and 4 year incidence of EAMs was calculated and comparative analyses regarding disease outcome was performed. Results: 421 axial SpA patients were included with a mean age of 43.4±12.5 years, 65% were male, mean symptom duration was 17.4±11.7 years, 78% were HLA-B27 positive, mean ASDAS was 3.3±1.1 and 66% started TNF-α inhibitors at baseline. Of the 421 patients, 132 (31.4%) had a positive history of one or more EAMs: 104 (24.8%) AAU, 40 (9.5%) IBD, and 18 (4.3%) psoriasis. Of the 362 patients with 4 year follow-up data, 57 (15.7%) patients developed an EAM: 48 (13.3%) patients AAU, of which 13 (3.6%) had a first episode, 7 (1.9%) patients developed IBD, and 3 (0.8%) patients developed psoriasis. Patients who developed a new EAM without a history of EAMs at baseline had higher ASQoL (mean 10.0 vs. 5.9, p=0.001), larger occiput to wall distance (median 6.3 vs. 2.0, p=0.021) and also the modified Schober test was more limited (mean 12.6 vs. 13.6, p=0.014) after 4 years of follow-up. The difference found for BASFI was not statistically significant (mean 4.4 vs. 3.4, p=0.12). Conclusions: The prevalence rates of EAMs in our cohort are similar as found in other axial SpA studies. The 4 year incidence of EAMs was relatively low, possibly due to the relatively large proportion of patients starting TNF-α inhibitors at baseline. However, these axial SpA patients showed worse quality of life and clinical outcome than patients without a newly developed EAM. Disclosure of Interest: R. van der Meer: None declared, S. Arends Grant/research support from: Pfizer, S. Kruidhof: None declared, R. Bos: None declared, H. Bootsma: None declared, F. Wink Consultant for: Abbvie, A. Spoorenberg Grant/research support from: Pfizer, Abbvie, Consultant for: Pfizer, Abbvie, MSD, UCB, Novartis